From popular movements to rebellion
1 online resource
Keywords: From Popular Movements to Rebellion: The Naxalite Decade argues that without an understanding of the popular sources of the rebellion of that time, the age of the Naxalite revolt will remain beyond our understanding. Many of the chapters of the book bring out for the first time unknown peasant heroes and heroines of that era, analyses the nature of the urban revolt, and shows how the urban revolt of that time anticipated street protests and occupy movements that were to shake the world forty-fifty years later. This is a moving and poignant book. Some of the essays are deeply reflective about why the movement failed and was at the end alienated. Ranabir Samaddar says that, the Naxalite Movement has been denied a history. The book also carries six powerful short stories written during the Naxalite Decade and which are palpably true to life of the times. The book has some rare photographs and ends with newspaper clippings from the period. As a study of rebellious politics in post-Independent India, this volume with its focus on West Bengal and Bihar will stand out as an exceptional history of contemporary times. From Popular Movements to Rebellion: The Naxalite Decade will be of enormous relevance to students and scholars of history, politics, sociology and culture, and journalists and political and social activists at large. Please note: Taylor & Francis does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka